ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA DITINJAU DARI GAYA BELAJAR - Muhammad Fuad Hidayatulloh; Denok Julianingsih (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2021)
The ability to think creatively is a person's ability to process and think of new solutions in the form of ideas or real results. In processing new ideas, a person has different ways according to his learning style. Analysis of creative thinking skills aimed to describe students' creative thinking skills concerned of student learning styles. The method of this study used qualitative. The subject of this research was VIII-A SMP NU Bahrul Ulum, Menganti, Gresik 2020-2021 academic year. There are three instruments such as learning style questionnaire, creative thinking ability test and interview guidelines. Learning style questionnaires were given to all students in grades VIII-A, at the same time creative thinking tests and interviews were only given to three students representing each learning style. The measurement of creative thinking skills uses three indicators, there are fluency indicators, flexibility indicators, and novelty indicators. There are five levels in creative thinking ability level, that is level 4 it said very creative, level 3 is creative, level 2 said to quite creative, level 1 it said less creative and level 0 stated uncreative. Based on the results of the study, the researcher concluded that subjects with visual learning styles reached level 2 which was quite creative, subjects with auditory learning styles accomplished level 3 which is creative, and subjects with kinesthetic learning styles attained level 4 which was very creative. Therefore, each learning style has a different level of creative thinking.